(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The relevance of coronavirus infection today remains extremely high and multifaceted. The global pandemic continues to have a significant impact on public health, economic development and social structures. Uneven distribution of vaccines, the emergence of new virus strains and changing public behavior pose additional challenges to health systems.